MEMBANGUN KEBERDAYAAN MASYARAKAT MELALUI PENINGKATAN KARAKTERISTIK INDIVIDU DI PAPUA - Indah Sulistiani; Sumardjo Sumardjo; Ninuk Purnaningsih; Basita Ginting Sugihen (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Empowerment is an internal power owned by the community in tackling the problems of social environment. Humans as social beings naturally interact and depend on one another in a dynamic social environment. Social energy development is largely determined by the characteristics of individuals to interact with each other. This study uses (Mixed methods) or a combination of methods of Creswell (2009) with the apprach of explanatory squential strategic.This research was conducted in two districts of Jayapura and Jayapura city in Papua with the intention to analyze the characteristics of individual communities and analyze the relationship of the individual characteristics of communities with community empowerment. The results showed (1) the individual characteristics of society in Papua include: education level, income level, the level of cosmopolitan and ownership of the means of communication is still relatively low, the level of motivation in the medium category, in the category of adult age, the majority work as a farmer / fisherman; (2) there is a relationship directly and indirectly characteristics of individual communities with community empowerment.